A Paradigm Shift on the Question of B Cells in Transplantation? Recent Insights on Regulating the Alloresponse - Firl, Daniel J.; Benichou, Gilles; Kim, James I.; Yeh, Heidi (Frontiers in Immunology, 2017)
Abstract B lymphocytes contribute to acute and chronic allograft rejection through their production of donor specific antibodies (DSA). In addition, B cells present allopeptides bound to self-MHC class II molecules and provide costimulation signals to T cells, which are essential to their activation and differentiation into memory T cells. On the other hand, both in laboratory rodents and patients, the concept of effector T cell regulation by B cells is gaining traction in the field of transplantation. Specifically, clinical trials using anti-CD20 monoclonal antibodies to deplete B cells and reverse donor specific antibody resulted in increased rates of acute cellular rejection; a peculiar finding which calls into question a central paradigm in transplantation. Additional work in humans has characterized IL-10 producing B cells (IgM memory and transitional B cells), which suppress the proliferation of and inflammatory cytokine production by effector T cells in vitro. Understanding the mechanisms of regulating the alloresponse is critical if we are to achieve operational tolerance across transplantation. This review will focus on recent evidence in murine and human transplantation with respect to non-traditional roles for B cells in determining clinical outcomes.